Anisotropic deformation characteristics of an ultrafine- and nanolamellar pearlitic steel. (March 2016) - Kapp, M.W.; Hohenwarter, A.; Wurster, S.; Yang, B.; Pippan, R.
Abstract: Micromechanical experiments with 3 × 3 × 6 μm 3 sized micro pillars were used to examine orientation dependencies of the mechanical properties in a severely plastically deformed high strength steel and compared with the undeformed state. For the synthesis, an initially ultrafine-lamellar (UFL) fully pearlitic steel was subjected to high pressure torsion (HPT) transforming the steel into a nanolamellar (NL) composite. Both microstructural states were then tested in-situ inside a scanning electron microscope. Within the individual micro pillars, fabricated by focused ion beam milling, the ferrite and cementite lamellae were aligned parallel, normal or inclined to the loading direction. The main findings are: First, the strength and strain hardening capacity is more than doubled comparing the UFL with the NL composite. Second, an anisotropic mechanical response exists in terms of i) strain hardening capacity and ii) stress level at the onset of plateau formation. Third, deformation and localization mechanisms at large compressive strains vary with the lamellae orientation, however they are independent of the lamellae thickness. Graphical abstract: